EVALUATION OF CHRISTIAN CHARACTER VALUE INTEGRATION WITHIN THE CHRISTIAN RELIGIOUS EDUCATION CURRICULUM AT THE PELALAWAN PLANTATION INSTITUTE OF TECHNOLOGY INDONESIA - Laurent Valencia Sitanggang; Wahyu Wijiati; Lydia Weniati Augustiana (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study evaluates the integration of Christian character values within the Christian Religious Education (PAK) curriculum at the Institut Teknologi Perkebunan Pelalawan Indonesia (ITP2I). The urgency of this research stems from the academic and moral decline among students, such as low discipline and a lack of structured learning modules, which hinders spiritual transformation. The research problems focus on how the character values are integrated across the context, input, process, and product dimensions, and how a structured module can be designed as a solution. Consequently, the study aims to analyze these four evaluation dimensions and formulate a structured PAK teaching module to optimize character development. Theoretically, this research benefits the enrichment of curriculum evaluation models in vocational technical institutions, while practically providing a standardized framework for lecturers to foster students' integrity. This study employs a qualitative descriptive approach utilizing Daniel L. Stufflebeam’s CIPP evaluation model. Data were gathered through documentation, observations, and semi-structured interviews with the Vice Rector, PAK lecturers, and students. The results indicate that character integration in the context dimension appears only symbolically. Input and process dimensions reveal that PAK instruction remains ad hoc and lacks standard modules, leading to fragmented character internalization. Furthermore, product evaluation lacks measured criteria. To overcome these deficits, this study designs a structured PAK module consisting of 16 comprehensive learning sessions covering biblical foundations, personal character development, and professional ethics tailored for the plantation sector. In conclusion, a structured learning tool is crucial to scaffolding moral development and achieving holistic student transformation.